Stressful Life Events, Internet Addiction, and Sleep Quality among Medical Students in a Tertiary Rural Hospital. - Gogate, Sonali; Nanaware, Sagar; Padma, Kumari (Indian Journal of Medical Specialities)
Background: Medical students experience substantial academic and psychosocial stress during their period of training, which, combined with lifestyle factors such as problematic Internet use, may adversely affect sleep quality and their overall mental health. Understanding the prevalence of these factors is critical for developing targeted interventions to support student well-being. Objectives: The objective of this study was to assess the prevalence of stressful life events, Internet use patterns, and sleep quality among undergraduate medical students, and to examine their relationships. Methodology: A cross-sectional study was conducted among 200 undergraduate medical students aged 17–25 years in a tertiary rural medical college. Participants completed validated questionnaires: The Pittsburgh Sleep Quality Index (PSQI), the Presumptive Stressful Life Events Scale, and Young's Diagnostic Questionnaire for Internet Addiction, anonymously through an online platform. Data were analyzed using descriptive statistics and Chi-square tests, with a P < 0.05 considered statistically significant. Results: Moderate to high stress was reported by 82.5% of students. Poor sleep quality (PSQI >5) was observed in 35.5% of participants. Nearly half of the students (49.0%) demonstrated some degree of Internet addiction. No statistically significant associations were found between sleep quality and stress levels or Internet addiction. Conclusion: High levels of stress, problematic Internet use, and poor sleep quality were prevalent among medical students. Although no significant associations were identified between these factors, the findings highlight the need for institutional strategies focusing on stress reduction, digital awareness, and sleep hygiene.